From the Role to the Function: Exploring the Meanings of the Tea Culture of Chinese Ethnic Minorities - Xia, Tian; Guang, Tian; Yangkuo, Li; Gang, Chen (Journal of Posthumanism, 2025)
Chinese tea culture has increasingly become a favored hot study subject at home and abroad. Through an in-depth systematic exploration of the literature on the tea culture of China’s ethnic minorities, this paper offers insight into its role and functions in the life and customs of contemporary China’s ethnic minorities. A content-based analysis methodology is adopted to demonstrate the panoramic past and present tea culture. The study finds that tea plays a significant and irreplaceable role in the economic and social life of China’s ethnic minorities, which are the birthplace of Chinese tea culture. The functions of tea drinking of ethnic minorities take shape under the interaction of extensive economic and cultural exchanges among various ethnic groups. This paper addresses the practical functions and values of tea culture so that China should strengthen the inheritance, development, and utilization of the excellent traditional culture of all ethnic groups, including tea culture, to be carried forward and produce economic benefits. It is of great practical significance to promote economic and cultural development under the tea culture of ethnic groups outside China. An ethnological and ethnographic exploration in the paper sheds some light on understanding Chinese tea culture and its contribution to the world culture, such as tea production, making, serving, and appreciation in the Chinese context.